Pengaruh Penambahan Sari Jeruk Nipis (Citrus aurantifolia) Terhadap Aktivitas Antioksidan Loloh Don Cemcem (Spondies pinnata (L.F) Kurz.) - Viranty, Ni Kadek Ayu; Sugitha, I Made; Wisaniyasa, Ni Wayan (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPA, 2024)
Loloh don cemcem is a traditional Balinese drink made from cemcem leaf extract with water (20%) and other additives such as sugar, salt, tamarind, cayenne pepper and coconut meat which have physiological effects on the body. Based on research conducted by Aryasa et al ., (2021), loloh don cemcem is known to have antioxidant activity of 23.50 mg/L GAEAC, with an IC50 value of 471.9440 ppm which is included in the class of very weak antioxidant activity. The addition of lime juice to loloh don cemcem is known to increase its antioxidant activity, this is because lime contains organic acids such as citric acid and ascorbic acid, wich have antioxidant properties. This study aims to determine the effect of the addition of lime juice on the antioxidant activity of loloh don cemcem and to determine the appropriate addition of lime juice to produce the highest antioxidant activity. This study used a completely randomized design with the addition of lime juice, namely 0%, 1%, 2%, 3%, and 4%. All treatments were repeated 3 times to obtain 15 experimental units. The data obtained was analyzed using ANOVA, and if there is a real influence, it will be followed by DMRT. The results showed that the addition of lime juice had a significant effect (P<0.05) on total acid, total vitamin C, total flavonoids, antioxidant activity, total microbes, hedonic taste test, overall acceptance and taste score. The addition of 4% lime juice had the highest antioxidant activity with the criteria of total acid 14.03%, total vitamin C 21.17 mg/100mL, total flavonoids 10.63 mg QE/100 mL, antioxidant activity 80.29%, IC50 71.190 ppm , total negative microbes, liked color, sour and liked taste, liked aroma and liked overall acceptance.